Why would Musical Training Benefit the Neural Encoding of Speech? The OPERA Hypothesis - Patel, Aniruddh D. (Frontiers in Psychology, 2011)
Mounting evidence suggests that musical training benefits the neural encoding of speech. This paper offers a hypothesis specifying why such benefits occur. The “OPERA” hypothesis proposes that such benefits are driven by adaptive plasticity in speech-processing networks, and that this plasticity occurs when five conditions are met. These are: 1) Overlap: there is anatomical overlap in the brain networks that process an acoustic feature used in both music and speech (e.g., waveform periodicity, amplitude envelope), 2) Precision: music places higher demands on these shared networks than does speech, in terms of the precision of processing, 3) Emotion: the musical activities that engage this network elicit strong positive emotion, 4) Repetition: the musical activities that engage this network are frequently repeated, and 5) Attention: the musical activities that engage this network are associated with focused attention. According to the OPERA hypothesis, when these conditions are met neural plasticity drives the networks in question to function with higher precision than needed for ordinary speech communication. Yet since speech shares these networks with music, speech processing benefits. The OPERA hypothesis is used to account for the observed superior subcortical encoding of speech in musically trained individuals, and to suggest mechanisms by which musical training might improve linguistic reading abilities.